WARTHIN’S TUMOUR OF FLOOR OF THE MOUTH - CORRELATION OF FNAC AND HISTOPATHOOGICAL FINDINGS - Bajpai, Manas; Pardhe, Nilesh; Kumar, Manish (Journal of Ayub Medical College Abbottabad, 2018)
A 43-year-old male presented to our institute with the chief complain of a painless swelling of floor of the mouth from 8 months. The swelling was initially small and gradually reached its current size. Personal history of the patient revealed the he had been consuming 8-10 cigarettes daily from 15 years. The family history and past medical history of the patient was non - contributory to the presenting symptom. Intra-oral examination revealed a solitary dome shaped soft and fluctuant tissue growth of the right side of the floor of the mouth extending from lingual mucosa with relation to the tooth #41 to tooth #44 measuring about 3Ã—2 cm. The colour of the overlying mucosa was similar to the adjacent mucosa without any sign of ulceration and discharge. [Figure-1a] FNAC was performed under aseptic condition. Smears were wet fixed immediately in ether-alcohol fixative and stained by Papanicolaou stain. The microscopic examination revealed a moderately cellular field comprised of single layered cohesive sheets of epithelial cells with focal collection of lymphocytes in a mucoid background. [Figure-1b] The epithelial cells were showing oncocytic pattern with densely eosinophilic granular cytoplasm with round nuclei. [Figure-1c] Based on cytopathological findings an initial impression of WT was made. The surgical excision of the lesion was done under general anaesthesia and the excised tissue was sent for histopathological evaluation. The histopathological examination of haematoxylin and eosin stained soft tissue section revealed cystic spaces densely filled with eosinophilic coagulum and surrounded by bilayered oncocytic epithelium arranged in papillary fronds. The inner cell layer was tall columnar and outer layer was oncocytic. These papillary fronds were surrounded by dense lymphocytic infiltrates. [Figure 1d] Based on histopathology a final diagnosis of Warthin’s tumour was given. Warthin’s tumours (WT) are most commonly found in parotid gland.1-3 They are the second most common tumours of parotid after pleomorphic adenoma.2 WT occurring in minor salivary gland of floor of the mouth is an exceedingly rare phenomenon. An exhaustive literature review has revealed a single published case of WT of floor of the mouth; hence the present case is being only the second case.3 The occurrence of Warthin’s tumour in minor salivary glands is extremely rare and the incidence was reported between 0.1-1.2%.1,2 The Incidence of WT commonly appears between ages of 58 and 70 years and can arise in adults; WT is more common in men than in women. Previous studies have shown a close association of WT with smoking. In present case also the patient was a chronic smoker.1-3 The accuracy of FNAC in diagnosis of salivary gland tumours is quite debatable among clinicians and cytopathologist. FNAC in WT may simulate many other conditions including oncocytoma, oncocytic carcinoma and lymphoepithellial cyst.1A proper care and knowledge pertaining to the limitations of cytology in diagnosing WT is needed.